2014
DOI: 10.1007/s40194-014-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of PC and PA6 during laser transmission welding

Abstract: Laser transmission welding (LTW) causes a temperature rise at the weld interface which leads to melting, molecular diffusion and ultimately joining of the two components. Weld temperatures increase with laser power at a given scan speed. However, at higher temperatures, it has been observed that weld strength starts to decline due to material thermal degradation. Thermal degradation is a kinetic phenomenon which depends on both temperature and time. Thermal gravimetric analysis (TGA) is used to study the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It was also found that increasing the proportion of PET in the blends resulted in more thermal degradation, and the blends containing PET achieved higher weld strength than pure PBT. The SB model, the nth-order model, and the 3D quasi-static finite element thermal model were combined by Bates et al [90] to simulate the thermal degradation of PC and PA6 in LTW. The study found that the power at which degradation begins decreases with ing absorber content, which is consistent with the power at which shear strength begins to decrease.…”
Section: Thermal Degradation Simulation In Ltwmentioning
confidence: 99%
“…It was also found that increasing the proportion of PET in the blends resulted in more thermal degradation, and the blends containing PET achieved higher weld strength than pure PBT. The SB model, the nth-order model, and the 3D quasi-static finite element thermal model were combined by Bates et al [90] to simulate the thermal degradation of PC and PA6 in LTW. The study found that the power at which degradation begins decreases with ing absorber content, which is consistent with the power at which shear strength begins to decrease.…”
Section: Thermal Degradation Simulation In Ltwmentioning
confidence: 99%
“…There is a considerable amount of research on the interaction between PA6 and other materials. However, the relatively weak bonding strength remains a major obstacle to its substitution of metal materials [4][5]. Therefore, studying ways to enhance the adhesive strength between reinforced resins becomes particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…6 Among them, polyamide 6 (PA6), as one of the most commonly used engineering polymer materials, has a wide range of applications in various industries, and there are many studies on the connection of PA6 itself and other materials. 7,8 However, the weak connection strength is a big obstacle preventing its replacement of metal materials. Therefore, it is particularly important to study the strengthening of the bonding strength between resins.…”
Section: Introductionmentioning
confidence: 99%
“…Considered together, these properties make thermoplastic resins an attractive option for combining with metal materials in multimaterial designs 6 . Among them, polyamide 6 (PA6), as one of the most commonly used engineering polymer materials, has a wide range of applications in various industries, and there are many studies on the connection of PA6 itself and other materials 7,8 . However, the weak connection strength is a big obstacle preventing its replacement of metal materials.…”
Section: Introductionmentioning
confidence: 99%